(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Folic acid, vitamins and Zinc play essential role in DNA methylation but alcohol consumption is known to affect the levels of these micronutrients leading to risk of developing various illnesses and certain cancers. This study determined the levels of DNA methylation dependent-micronutrients (folate, vitamin B12, vitamin B6, zinc and selenium) and homocysteine as a suggestion for DNA methylation status in Nigerian alcohol consumers compared with non-consumers of alcohol. Venous blood (5ml) was obtained from thirty-four males that consume alcoholic beverages for at least 10 years and thirty-two male controls that did not consume alcoholic beverages at least 10 years. Serum concentrations of folate, vitamin B12, vitamin B6, homocysteine (Hcy), selenium (Se) and zinc (Zn) were determined using High Performance Liquid Chromatography (HPLC) and Atomic Absorption Spectrophotometry (AAS) as appropriate. Independent Student t-test was used to compare the mean values between alcohol consumers and control. Mean differences were considered significant at p<0.05. The mean serum levels of Zn and Se were significantly raised in alcohol consumers when compared with non-alcohol consumers while the mean levels of Vitamin B6 and Hcy were significantly reduced in alcohol consumers when compared with non-alcohol consumers. There were no statistically significant differences in the mean serum levels of Vitamin B12 and folate in alcohol consumers when compared with non-alcohol consumers. Since vitamin B6 and Hcy are required for DNA methylation, reduced vitamin B6 and Hcy levels in consumers of alcoholic beverages might suggest DNA hypomethylation in alcohol consumers.